2009
DOI: 10.1179/136485909x398249
|View full text |Cite
|
Sign up to set email alerts
|

Antifilarial drugs, in the doses employed in mass drug administrations by the Global Programme to Eliminate Lymphatic Filariasis, reverse lymphatic pathology in children withBrugia malayiinfection

Abstract: Lymphatic filariasis is increasingly viewed as the result of an infection that is often acquired in childhood. The lymphatic pathology that occurs in the disease is generally believed to be irreversible. In a recent study in India, Doppler ultrasonography and lymphoscintigraphy were used to explore subclinical pathology in 100 children from an area endemic for Brugia malayi infection. All the children investigated showed some evidence of current or previous filarial infection. Some were microfilaraemic but asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Recent clinical research using ultrasonography and lymphoscintigraphy has documented the reversal of early lymph-vessel damage in Brugia malayi-infected children after MDA with DEC in India. 21 However, earlier studies in Brazil have failed to find a decrease in lymphatic vessel dilation after treatment with DEC in adults infected with Wuchereria bancrofti. 22,23 Of the 13 published studies assessing the effect of DEC on lymphedema-specific filarial morbidity, nine found a beneficial effect of DEC on lymphedema 20,24 -31 and the other studies demonstrated no effect.…”
Section: Introductionmentioning
confidence: 94%
“…Recent clinical research using ultrasonography and lymphoscintigraphy has documented the reversal of early lymph-vessel damage in Brugia malayi-infected children after MDA with DEC in India. 21 However, earlier studies in Brazil have failed to find a decrease in lymphatic vessel dilation after treatment with DEC in adults infected with Wuchereria bancrofti. 22,23 Of the 13 published studies assessing the effect of DEC on lymphedema-specific filarial morbidity, nine found a beneficial effect of DEC on lymphedema 20,24 -31 and the other studies demonstrated no effect.…”
Section: Introductionmentioning
confidence: 94%
“…Recent findings of reversibility of early lymphatic pathology in treated children provide ample proof that both the MDA strategy and 'foot-hygiene' measures can be viewed as an effective measure in preventing and managing morbidity. Programme managers should effectively utilize this information to strengthen their advocacy efforts to achieve high and sustainable coverage in MDA (Shenoy et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Due to the adverse effects that doxycycline is known to cause, this drug is generally not used in pregnant women and children (Taylor et al 2010). It may be recalled here that in a recent study on BM infection in children the presently available anti-filarial drugs are generally well tolerated and effective in clearing microfilaraemia and the FDS indicating presence of live adult worms and also in reversing the early subclinical lymphatic pathology (Shenoy et al 2009). …”
Section: Management Of Lf Infection and Disease In Childrenmentioning
confidence: 99%
See 2 more Smart Citations